Analysis of The Final School Test Question Instrument for Islamic Religious Education and Ethics - Nurul Husna; Nina Nurmila; Chaerul Rochman; Mulyawan; Gina (Educan : Jurnal Pendidikan Islam, 2023)
Developing question instruments in learning is a skill educator and prospective educators must master. A test instrument is said to be of quality if the question contains several components, including the question stimulus, there is a STEM (question), homogeneity of answers, an alternative formulation of question indicators, context, content, and cognitive level. This study aims to determine the quality of the question components, including the question stimulus, answer homogeneity, context, and mental status of the question. The method used is an analysis of the PAI end-of-semester exam questions and Ethics for the 2022/2023 IX odd semester academic year, namely seeing and analyzing question instruments, including question stimulus, answer homogeneity, context, and cognitive level of the question. The results showed that the question stimulus needs further development, while the uniformity of the answers has met good quality. Based on the cognitive level, questions generally are still categorized as LOTS compared to questions with HOTS categories.